Learning from failure: inadequate value propositions in an innovative approach to patient safety using a hand washing compliance auditing system. (2018) - DeForge, Ryan T.; Snowdon, Anne; MacLeod, Mark
This study examined how a hand washing compliance auditing system affects physician hand washing compliance and rates of hospital acquired infections. Ultimately, data collection was significantly impaired by low recruitment and compliance rates. To learn from this project's failure, medical residents were invited to participate in an interview to discuss the project, its merits and shortcomings. Beyond existing resistance to such surveillance, study procedures, confounding contextual variables and insufficient value propositions seem to account for the project's failure. Use of a hand washing compliance auditing system is likely to fail if it is not optimally integrated into existing clinical workflows and hospital infrastructure, or if auditing seems to take the form of surveillance. Beyond the establishment of proof of concept, proof of relevance and value for all stakeholder groups must be established to embed an innovation such as this hand washing compliance auditing system.